2019
DOI: 10.1021/acs.jmedchem.9b00964
|View full text |Cite
|
Sign up to set email alerts
|

Structure Defines Function: Clinically Relevant Mutations in ErbB Kinases

Abstract: The ErbB receptor tyrosine kinase family members EGFR (epidermal growth factor receptor) and Her2 are among the prominent mutated oncogenic drivers of non-small cell lung cancer (NSCLC). Their importance in proliferation, apoptosis, and cell death ultimately renders them hot targets in cancer therapy. Small-molecule tyrosine kinase inhibitors seem well suited to be tailor-made therapeutics for EGFR mutant NSCLC; however, drug resistance mutations limit their success. Against this background, the elucidation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 95 publications
0
10
0
Order By: Relevance
“…Osimertinib employs an anilinopyrimidine core that makes two H-bonding interactions with the backbone of Met793, and an indole side chain that forms van der Waals interactions with various hydrophobic side chains from the P-loop, to allow the indole ring to point away from Thr790, leaving the space between Lys745 and Thr790 largely unoccupied (Figure A). However, the quinazoline-based first- and second-generation EGFR TKIs bind to WT EGFR in an extended conformation, with the substituted benzene ring positioned between Lys745 and Thr790 (Figure B). , On the basis of these crystal structures, the T790M mutation is more likely to disrupt the binding of first- and second-generation EGFR tyrosine kinase inhibitors due to steric clash but allows the Met790 side chain to make favorable hydrophobic interactions with the edge of the pyrimidine-indole ring of osimertinib, which likely confers the decreased off rate of osimertinib from the reversible EI complex with L858R/T790M EGFR. This is in broad agreement with the proposed T790M mutant selectivity mechanism for WZ4002, an earlier example of a third-generation EGFR TKI, and a reversible EGFR inhibitor using the osimertinib scaffold with a chlorine-substituted pyrimidine ring …”
Section: Discussionmentioning
confidence: 99%
“…Osimertinib employs an anilinopyrimidine core that makes two H-bonding interactions with the backbone of Met793, and an indole side chain that forms van der Waals interactions with various hydrophobic side chains from the P-loop, to allow the indole ring to point away from Thr790, leaving the space between Lys745 and Thr790 largely unoccupied (Figure A). However, the quinazoline-based first- and second-generation EGFR TKIs bind to WT EGFR in an extended conformation, with the substituted benzene ring positioned between Lys745 and Thr790 (Figure B). , On the basis of these crystal structures, the T790M mutation is more likely to disrupt the binding of first- and second-generation EGFR tyrosine kinase inhibitors due to steric clash but allows the Met790 side chain to make favorable hydrophobic interactions with the edge of the pyrimidine-indole ring of osimertinib, which likely confers the decreased off rate of osimertinib from the reversible EI complex with L858R/T790M EGFR. This is in broad agreement with the proposed T790M mutant selectivity mechanism for WZ4002, an earlier example of a third-generation EGFR TKI, and a reversible EGFR inhibitor using the osimertinib scaffold with a chlorine-substituted pyrimidine ring …”
Section: Discussionmentioning
confidence: 99%
“…Although no one succeed to gain crystal structures of EGFR-Del19 mutants, recent in silico molecular dynamics (MD) simulations revealed that Del19 mutations inferred that the reduced length and flexibility of N-terminal portion of aC-helix locks the helix αC-in state and prohibits transition to the inactive conformation. The EGFR structure (PDB IB: 1M17) is reported as a similar αC-helix-in structure to that of Del19 by MD simulation (44), and so we additionally superimposed our crystal structure (PDB ID: 6LUB) with this crystal structure (PDB ID: 1M17). As shown in revised Supplementary Fig.…”
Section: Ch7233163 Displayed Unique Interactions With Triple-mutated mentioning
confidence: 99%
“…About 80% of mutations that occur in Her2 are insertions that affect the beginning of the helix αC. , Most frequently found was the A775_G776insYVMA mutation that results in duplication of the YVMA motif (Figures A and S1). An accepted theory is that mutations in exon 20 induce a stabilized active conformation of the regulatory helix, thereby increasing the kinase activity which finally results in the onset of the RAS–RAF–MEK–ERK pathway that regulates cell proliferation and survival. , Moreover, signaling through amplified Her2 has been reported to be a mechanism of resistance toward the treatment of mutant EGFR with small-molecule tyrosine kinase inhibitors (TKIs) . Afatinib ( 1 ), , poziotinib, dacomitinib, , neratinib ( 2 ), and lapatinib ( 3 ) have been evaluated as TKIs targeting Her2.…”
Section: Introductionmentioning
confidence: 99%